The application of the fuzzy aggregation norms to technical staff tasks delegation - Aleksandra Mrela; Oleksandr Sokolov; Grzegorz Śmigielski; Oleksii Sokolov; Szymon Uczciwek (Kazimierz Wielki University, 2019)
The methods for calculating professional competence levels of technicians based on fuzzy relations and the optimistic fuzzy aggregation norm has been proposed. Since it is difficult to estimate levels of professional competence of all tasks by all members of a team of technicians, the proposed method depends on a sequence of fuzzy relations which values are relatively easy to estimate and which the S-T-compositions produces the fuzzy relation of professional competence of all technicians. The proposed method is compared with the application of Minkowski metrics which is one of the objective methods of searching the best object in multi-criteria decision systems. Based on these two methods, the ranking of technicians can be prepared. Moreover, the method of results visualization is proposed.